An investigation into the floatability of platinum group arsenides and tellurides under varying collector and solution chemistries - Wali, Avuyile (Department of Chemical Engineering, 2025)
Platinum group tellurides and arsenides are the most economically important and abundant platinum group minerals (PGM) in the Platreef ore deposit. It has been found that there are major losses of these minerals during flotation, with most of the losses attributed to sperrylite (PtAs2). This study has investigated the use of collectors with greater electron-donating properties such as trithiocarbonate and thiourea collectors under the assumption that these collectors would bond more readily with the sperrylite surface and induce floatability of this mineral to a greater extent compared to the traditionally used xanthate collectors. Although the trithiocarbonate and thiourea collectors did adsorb more strongly on the sperrylite surface which was shown using microcalorimetry, none of the collectors significantly improved the floatability of sperrylite at pH 9 and a dosage equivalent to 1 pseudo-monolayer (ML) surface coverage. Higher dosages of a strong collector, potassium amyl xanthate (PAX), improved the recovery of sperrylite only up to 45% at 20 ML from 15.4% at 1 ML. To gain further understanding, the floatability of sperrylite was investigated under varying pH and Eh conditions and this was compared with other similar PGMs such as palladoarsenide (Pd2As), moncheite (PtTe2) and merenskyite (PdTe2). In the presence of PAX at pH 9, the microflotation recoveries of the minerals followed the order: Pd₂As (95%) > PtTe₂ (88%) > PdTe₂ (81%) > PtAs₂ (22%). Spectroscopic studies performed in this study showed, for the first time, that sperrylite has a greater affinity for the adsorption of OH- and H2O compared to the other PGMs investigated, which contributes to the poor floatability of this mineral. Another major contributing factor to the poor floatability of sperrylite was proposed to be its weaker electrochemical interaction with xanthates due to its poor electron-conducting properties. Operating under acidic conditions significantly improved the interaction of sperrylite with xanthates, hence its floatability. In the presence of PAX at pH 3, the microflotation recoveries of the minerals followed the order: PtTe₂ (91%) > PdTe₂ (90%) > Pd₂As (85%) > PtAs₂ (61%). This was corroborated by batch flotation studies which showed that the flotation performance of platinum group arsenides from a Platreef ore (which are dominated by sperrylite) can be selectively improved by operating at pH 3 even in the presence of froth effects, a complex ore, and complex cell hydrodynamics. This study contributes to the fundamental understanding of the interactions of platinum group minerals with water, hydroxide species and collectors. In particular, this study contributes to the understanding of the poor floatability of sperrylite, a major component of the largest PGM ore body in the world, and possible remedies for improving its floatability.